Structure Design and Performance Analysis of a Novel Pole-climbing Robot - Bao Xiulan; Wang Lintao; Huang Jiayun; Gan Di; Huangfu Jixuan; Mao Jincheng (Jixie chuandong)
A novel pole-climbing robot is proposed for the cleaning and maintenance of urban pole-shaped buildings,by using a drive mechanism to complete the movement and clamping. The gait of the robot during climbing process is studied. The virtual prototype of the climbing robot is established. The climbing process of the robot is simulated by using ADAMS,which is multi-rigid body dynamics simulation software.The changing situation of displacement of the robot,torque of the motor and gripping force of the manipulator are analyzed. The simulation results show that the robot can complete the smooth movement according to the intended direction. The motor torque has fluctuation,but the climbing stability of the robot is not affected. The average contact force between the unilateral manipulator and the lamp poles is 32. 4 N. The robot has a good adaptability for the diameter variation of poles.